HUBUNGAN KEPUASAN PENAMPILAN MAKANAN DENGAN SISA MAKANAN MENU SAYUR PADA PASIEN RAWAT INAP KELAS III DI RUMAH SAKIT KRISTEN MOJOWARNO - Rizka Mar'atus sholichah (STIKES dan AKZI Karya Husada Kediri, 2023)
One of the nutritional service problems in hospitals that often occurs is the amount of plate waste from patients. The plate waste can be used as an indicator of the nutritional service quality and also can be used to assess hospital food standards. The high plate waste causes inadequate food intake so that it has an impact on the length of treatment days. In the preliminary survey, the plate waste at Mojowarno Christian Hospital reached 39.79% which had not yet reached the Minimum Service Standards (≤ 20%). The purpose of this research was to determine the connection between food appearance satisfaction and vegetable plate waste in third class inpatient room at Mojowarno Christian Hospital. This research is an observational study with a cross-sectional approach. The number of samples was 28 with a duration of 3 days minimum treatment. The collected data related to the food appearance included the color, shape of the food, the portion, and the way of serving the food which was obtained through a questionnaire, as well as the data of waste food obtained from the Comstock method. The data obtained were analyzed using the Spearmen Rank test (α = 0.05). The results of the univariate analysis of the average frequency of distribution of vegetable plate waste in the third class inpatient room at Mojowarno Christian Hospital was 32.7%. Bivariate analysis showed that there was a connection between color satisfaction (p = 0.022), shape of food (p = 0.016), portion (p = 0.045), and presentation method (p = 0.032) with vegetable plate waste in third-class inpatients at the Mojowarno Christian Hospital. If the patient is satisfied with the appearance of the food on the vegetable menu, there will be less plate waste on the vegetable menu.